La utilización de un modelo de planificación de unidades didácticas: el estudio de las disoluciones en la educación secundaria - Sánchez Blanco, Gaspar; Pro Bueno, Antonio de; Valcárcel Pérez, María Victoria (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
The planning of didactic units is an element of reflection for teachers which allows the integration of both their scientific knowledge and their experiential skills. This study focus on the implementation of a planning model based on five tasks; the analysis of scientific content and the learning content which is derived from it (conceptual, procedural and attitudinal), the analysis of the problems involved in the learning of it (previous ideas and operational skills), the setting of the learning aims, the selection of the didactic strategies and the establishment of evaluative strategies. The model is applied to the Solutions in Secondary School.